Analisis Kualitas Sistem Informasi Akademik Universitas Tridinanti Menggunakan Model Kualitas McCall - Dunita Salsabila Assyifa; Ahmad Farisi (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2026)
The Academic Information System (AIS) of Tridinanti University plays a crucial role in integrating various academic and institutional administrative data. However, the operational effectiveness of this system is often hampered by technical obstacles such as slow access (server downtime) during peak usage and data synchronization problems. This study aims to objectively assess the operational feasibility of the AIS using the McCall Quality Model, with a specific focus on the product operations dimension. Primary data collection was conducted through the distribution of digital questionnaires to 60 active user respondents using the Simple Random Sampling technique. The analysis results show that the total percentage of operational feasibility of the AIS reached 90.66%, which is included in the Excellent category. Measurement of the five quality factors produced high scores: Usability obtained the highest score (4.58), followed by Correctness (4.55), Efficiency (4.52), Integrity (4.52), and Reliability (4.49). In conclusion, the AIS has been operating optimally for all its users. However, the institution is advised to increase the capacity of the server infrastructure to avoid technical disruptions and optimize the internal search function for more precise data tracking. Therefore, an upgrade in IT infrastructure governance through regular preventive maintenance is requ'ired to maintain system operational sustainability.